2008
DOI: 10.1177/0739986307311255
|View full text |Cite
|
Sign up to set email alerts
|

Identity and Language

Abstract: Language is an important marker of identity. Guided by social identity theory and using a grounded theory approach, this study examined how languages are chosen and shape experiences in the workplace. Results suggest that language use is influenced by both external (norms, business needs) and internal (identity, language comfort) processes. Furthermore, speaking Spanish in the workplace has both positive (inclusion, camaraderie) and negative effects (exclusion, harassment, discrimination), with many more negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 42 publications
(85 reference statements)
2
7
0
Order By: Relevance
“…They found that language plays an important role in the way immigrants are treated in the workplace and concluded that Hispanic employees faced exclusion, harassment and discrimination if they spoke Spanish at the workplace. They also suggested that speaking Spanish appeared to mark the speaker as an outsider (Bergman et al, 2008). Similarly, Lønsmann's (2014) study of international employees, who were experts in their fields e.g.…”
Section: Social Integration and Local Language Skillsmentioning
confidence: 99%
See 4 more Smart Citations
“…They found that language plays an important role in the way immigrants are treated in the workplace and concluded that Hispanic employees faced exclusion, harassment and discrimination if they spoke Spanish at the workplace. They also suggested that speaking Spanish appeared to mark the speaker as an outsider (Bergman et al, 2008). Similarly, Lønsmann's (2014) study of international employees, who were experts in their fields e.g.…”
Section: Social Integration and Local Language Skillsmentioning
confidence: 99%
“…However, some studies also traced other factors such as racial discrimination and ethnicity based stereotyping as contributing to social exclusion of immigrants, particularly in case of those belonging to visible minority. For instance, Bergman et al (2008) related weak local language skills to social exclusion, harassment and discrimination. But, they also suggested that appearance and ethnicity based maltreatment are also important to understand the phenomenon.…”
Section: Accent Discriminationmentioning
confidence: 99%
See 3 more Smart Citations